Hydroponics in jail - Hannah Wooten (Urban Food Systems Symposium, 2020)
According to a study by the Bureau of Justice Statistics, 83% of state prisoners were arrested at least once within nine years following their release. Reducing recidivism rates by providing educational training is one method to reduce the tendency of a criminal to reoffend. Only 7% of local correctional facilities provide vocational training for the incarcerated population. Correctional facilities in urban areas have the capacity to provide vocational training to inmates in urban agricultural techniques. The John E. Polk Correctional Facility in Seminole County, Florida maintains a partnership with University of Florida/Institute of Food and Agricultural Sciences (UF/ IFAS) Extension to provide vocational training to female inmates in greenhouse production of hydroponic fruits and vegetables. The partnership consists of a 5-day, 26-hour, intensive classroom and hands on training in the hydroponic greenhouse. Since the first pilot program in August of 2017, 117 women have earned a Certificate of Completion in Hydroponic Production of Fruits and Vegetables. End of program evaluations (n= 77) indicate 100% increased knowledge on hydroponic growing, systems, and integrated pest management (IPM), 98% received the Certificate of Completion, and 92% would consider a career working with plants. Participant follow up indicates at least one participant has accepted a job as Assistant Grower, and another participant has started her own microgreens business. Here is a video capturing the program impacts https://www.youtube.com/watch?v=XAR6Jr77p7Q. Deputies provide anecdotal evidence of reduced recidivism saying they do not see the women that participate in the hydroponics program return in as great of frequency as other inmates. Qualitative data indicates that the training program increases morale, boosts self-confidence, and prompts interest in learning. The correctional facility greenhouse sells 9,000 in produce annually to the cafeteria increasing the amount of fresh produce being served to both the deputies and the inmates. Partnering with correctional facilities has beneficial teaching, learning, and revenue enhancing opportunities. The program is on-going with future goals to collect long term data on recidivism rates, while increasing the productivity of the hydroponic greenhouse.
Keywords: recidivism; inmate; corrections; vocational training; greenhouse; horticulture